Why women remain in abusive relationships? - Deza Villanueva, Sabina (2012)
This article presents a number of factors associated with the presence of women in domestic violence relationships. As is emphasized that violence against women by their partners or ex is characterized by elements that differentiate it from other types of interpersonal violence. It explicitly revictimación risks and establishing dynamic relationships of violence too long So are some explanatory theories and their effects: The cycle of violence, the learned hopelessness, paradoxical adaptation syndrome to violence and the Post Traumatic stress disorder